Analisis Problematika PAI Dan Solusinya Dalam Menghadapi Era Globalisasi Dan Era Industri 4.0 - Bima Fandi Asy'arie; Mulyadi Mulyadi (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The purpose of this research is to understand the problems faced by teachers in Islamic religious education, the various problems faced by teachers in schools, and how solutions to these problems can be applied in facing the era of industry 4.0 and globalization. The author uses a qualitative approach in library research, with research data derived from various literatures, such as journals, books, personal documents, and so on. The research objectives are (1) to understand Islamic religious education in the era of globalization and the industry 4.0 era, (2) to understand the problems of Islamic religious education and how to solve them. The results of this study focus on internal factor problems which include (1) mastery of material, (2) love for the teaching profession, (3) teaching skills, (4) student learning evaluations. Then the problems of external factors are (1) class management, (2) application of learning methods and models, (3) interaction between teachers and students, (4) use of instructional media